2017
DOI: 10.1111/lam.12724
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Escherichia coli in husbandry animals: the African perspective

Abstract: In the last few years, different surveillances have been published in Africa, especially in northern countries, regarding antimicrobial resistance among husbandry animals. Information is still scarce, but the available data show a worrying picture. Although the highest resistance rates have been described against tetracycline, penicillins and sulphonamides, prevalence of plasmidmediated quinolone resistance genes and extended spectrum b-lactamase (ESBL) are being increasingly reported. Among ESBLs, the CTX-M-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
106
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 86 publications
15
106
2
Order By: Relevance
“…E. coli and Klebsiella spp. are cause of mastitis in dairy cattle, but most often livestock animals are asymptomatic carriers of ESBLs producers [54,187]. The first ESBL-producing E. coli was isolated from a dog with urinary tract infection and it carried SHV-12 [188].…”
Section: Amr-genes In Gram-negative Bacteria From Animalsmentioning
confidence: 99%
“…E. coli and Klebsiella spp. are cause of mastitis in dairy cattle, but most often livestock animals are asymptomatic carriers of ESBLs producers [54,187]. The first ESBL-producing E. coli was isolated from a dog with urinary tract infection and it carried SHV-12 [188].…”
Section: Amr-genes In Gram-negative Bacteria From Animalsmentioning
confidence: 99%
“…In Rwanda, studies on antibiotic resistance in poultry (Omulo et al, 2015) are scarce. But in other African countries, several studies have established the prevalence of resistant E. coli strains in poultry farms (Kikuvi et al, 2006;Majalija et al, 2010;Naliaka, 2011;Hamisi et al, 2012;Alonso et al, 2017). Other studies showed differences in the antibiotic resistance of E. coli between various farming systems (Okoli, 2006;Naliaka, 2011;Rugumisa et al, 2016).…”
mentioning
confidence: 99%
“…Colistin is one of the most effective peptide antibiotics against multidrug-resistant (MDR) gram-negative bacteria [25]. It has been used as a feed antibiotic additive for animals in China since 1986.…”
Section: Discussionmentioning
confidence: 99%